Activation of alkynes with B(C6F5)3: boron allylation reagents derived from propargyl esters - Hansmann, Max M.; Melen, Rebecca L.; Rominger, Frank; Hashmi, A. Stephen K.; Stephan, Douglas W. (Journal of the American Chemical Society, 2014)
Novel allyl boron compounds are readily synthesized via rearrangement reactions between Lewis acidic B(C6F5)3 and propargyl esters. These reactions proceed through an initial cyclization followed by ring-opening and concurrent C6F5-group migration. In the absence of disubstitution adjacent to the ester oxygen atom, an allyl boron migration rearrangement leads to formal 1,3-carboboration products. These allyl boron compounds act as allylation reagents with aldehydes introducing both a C3-allyl fragment and a C6F5-unit as a single anti-diastereomer. In these reactions, B(C6F5)3 activates the alkynes, prompting the rearrangement processes and enabling installations of C6F5 and R-groups.
Im Titel sind die Ziffer "6" "5" "3" tiefgestellt
Published: December 19, 2013
Gesehen am 29.10.2020